Building Resilient Small Businesses: The Role of Leadership in Crisis Management - Lisa Thompson; Mark Rivera; John Allen (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This research explores how leadership practices contribute to the resilience of small businesses during crises. Through case studies of SMEs (small and medium enterprises) affected by economic downturns and disruptions, the study highlights strategies such as resource optimization, strategic partnerships, and effective communication. Findings reveal that proactive leadership ensures business continuity and recovery.